2018
DOI: 10.1007/s11356-018-3621-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the content, occurrence, and leachability of arsenic, lead, and thallium in wastes from coal cleaning processes

Abstract: The aim of the study was to evaluate the content, occurrence, and leachability of arsenic (As), lead (Pb), and thallium (Tl) in wastes from coal cleaning processes with respect to the safe management of this waste. The study focused on wastes resulting from the wet gravitation and flotation processes employed for the purposes of coking coal cleaning in four coal mines situated in the Upper Silesian Coal Basin (Poland). The scope of the study included (i) determination of the content of these elements in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The ET AAS showed a LOQ between 0.05 and 10.00 μg L -1 in liquid samples and between 50.0 and 1,000 μg kg -1 in solids (Table 2). Studies using the same technique also present similar results in liquids ranging from 0.006 μg L -1 (Hassanpoor et al, 2015) and 4.60 µg L -1 (Makowska et al, 2018). In solid samples (soils), Nielsen et al (2011) obtained a considerably lower value (7.40 μg kg -1 ) than the present data survey.…”
Section: Resultssupporting
confidence: 83%
“…The ET AAS showed a LOQ between 0.05 and 10.00 μg L -1 in liquid samples and between 50.0 and 1,000 μg kg -1 in solids (Table 2). Studies using the same technique also present similar results in liquids ranging from 0.006 μg L -1 (Hassanpoor et al, 2015) and 4.60 µg L -1 (Makowska et al, 2018). In solid samples (soils), Nielsen et al (2011) obtained a considerably lower value (7.40 μg kg -1 ) than the present data survey.…”
Section: Resultssupporting
confidence: 83%
“…Furthermore, it was found that other ecotoxic elements are also adsorbed in large quantities on the surface of chimney soot, e.g. As, Pb, Cu, Zn, Ni, Cr (Chyc and Burzała 2012 ), which are commonly present in hard coal (Makowska et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…These elements, generally, can be removed from coal sufficiently (up to 80%), through applying gravity separation and/or flotation (Liu et al, 2019;Makowska et al, 2014;Mohanty et al, 1998;Parzentny, 1995). However, quite often the content of the elements in processed coal is still higher than the average content of the elements in hard coals from around the world (Chen et al, 2017;Duan et al, 2018aDuan et al, , 2018bDai et al, 2020b;Liu et al, 2019;Makowska et al, 2018;. Removing these elements from macerals and submicroscopic minerals of the elements from coal, through gravity separation and flotation, is considered to be ineffective and improbable.…”
Section: Vtmentioning
confidence: 99%